Digital Transformation and Human Resource Development for Operational Performance: A PLS-SEM Approach - Taufiqurrahman Hasibuan; Abdurrozzaq Hasibuan; Suhela Putri Nasution (Universitas Harapan Medan, 2026)
This study investigates the structural relationships between Digital Transformation, Human Resource Development, and Operational Performance using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach. The research aims to examine how digital initiatives and human resource capability development contribute to improving operational performance in organizations. Data were collected from 200 respondents involved in operational and digital transformation activities. The results indicate that Digital Transformation significantly enhances Operational Performance by improving process efficiency, flexibility, and productivity through the integration of digital technologies and data-driven decision systems. Human Resource Development also has a significant positive effect on Operational Performance by strengthening employee competencies, training effectiveness, and learning culture. In addition, Human Resource Development significantly influences Digital Transformation, indicating that employee readiness and capability are critical factors for successful digital implementation. The structural model demonstrates strong explanatory power and predictive relevance, indicating that the integration of technological transformation and human capital development plays an important role in improving operational performance. These findings provide managerial insights for organizations seeking to align digital transformation strategies with human resource development initiatives to achieve sustainable operational improvements.